PEMIKIRAN KALIGRAFI ARAB DI INDONESIA - M. Farkhan Mujahidin (CMES (Center of Middle Eastern Studies), 2016)
Arabic calligraphy as an art form distinctively Islamic in its development continues to progress, both in terms of form, writing, style, visualization, and media usage trends. Research on Arabic calligraphy is intended to determine the development of Arabic calligraphy in Indonesia by presenting a glimpse of history in the Middle East until in Indonesia. Data were obtained from a review of literature and direct observation, as well as the sources of literature and internet, studies done using qualitative methods based on quantitative data obtained. Results showed that the development of Arabic calligraphy in Indonesia towards metamorphosis, transformation and paradigm forms in accordance with the spirit of the age. Changes in cultural traditions characterized by the development of civilization increasingly open and reveal that calligraphy in Indonesia continues to grow following the movement of culture in other aspects of the broader, he was instrumental not only in the frame of the architecture of religious buildings, but he has been included in the development of eco-architecture today central to the social needs of society.